PEDAGOGICAL CONFLICT – THE CONTEMPORARY TECHNOLOGY OF THE COMPETENCY-BASED APPROACH - Chehlova, Zoja; Chehlov, Mihail; Gode, Ina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
In the 21st century, the creative role of education in the socio-economic development is increasing. Therefore, education is focused not only on the acquisition of certain amount of knowledge by learners, but also on the development of creative abilities and personal qualities, including the ability and desire to study, the ability and desire to act and the ability and desire to create. These key competencies develop in the process of learning on the basis of the technologies of the competency-based approach.The research problem is the development of positive learning motivation for students as the means of transforming inter-personal conflict into pedagogical conflict, which promotes individual’s moral education. The aim of the article is to analyse the characteristics of pedagogical conflict and elaborate the model of pedagogical conflict on this basis as a contemporary technology of the competency-based approach. The methodology of the research include: the competency-based approach and the activity-based approach;the research methods include: theoretical analysis, interpretation and mathematical statistics.The results of the study – there have been elaborated the theoretical basis of the pedagogical conflict as a technology of the competency-based approach:the nature of the has been analysed, and the content model of pedagogical conflict has been elaborated; there has been determined the organization of the process of learning based on the humanitarian inter-action of teachers and learners, which facilitates the transformation of inter-personal conflict into pedagogical conflict and promotes the moral education of an individual.